2013
DOI: 10.1590/0103-6440201302163
|View full text |Cite
|
Sign up to set email alerts
|

Apical Barrier Formation After Incomplete Orthograde MTA Apical Plug Placement in Teeth with Open Apex - Report of Two Cases

Abstract: Two cases are reported in which incomplete placement of 4 mm mineral trioxide aggregate (MTA) plug was performed unintentionally at the apical third of permanent immature teeth with open apex and apical periodontitis. As confirmed radiographically, there were gaps between MTA and dentinal walls along the MTA-dentin interface. After setting of MTA was confirmed, endodontic treatment was completed and access was sealed with composite resin. At 6 to 16 months follow-up examinations, formation of dentin in contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Several studies have reported that MTA yielded a significantly higher frequency of mineralized bridge formation, thicker and less porous dentin, and less periapical inflammation than calcium hydroxide 5,6) . It has also been reported that MTA induces migration and proliferation of osteogenic and odontoblastic cells, which, in turn, promotes mineralized tissue deposition, reducing inflammation in its site of action 4,6,8) . Such a protocol, combining the use of these two biomaterials (calcium hydroxide and MTA) in treating teeth with incomplete root formation, has been reported to offer favorable outcomes [1][2][3] , and the present results support the findings of these earlier studies.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Several studies have reported that MTA yielded a significantly higher frequency of mineralized bridge formation, thicker and less porous dentin, and less periapical inflammation than calcium hydroxide 5,6) . It has also been reported that MTA induces migration and proliferation of osteogenic and odontoblastic cells, which, in turn, promotes mineralized tissue deposition, reducing inflammation in its site of action 4,6,8) . Such a protocol, combining the use of these two biomaterials (calcium hydroxide and MTA) in treating teeth with incomplete root formation, has been reported to offer favorable outcomes [1][2][3] , and the present results support the findings of these earlier studies.…”
Section: Discussionmentioning
confidence: 97%
“…It is a calcium silicatebased cement composed of a mineral powder of hydrophilic particles which sets in the presence of moisture 6) . Several studies have reported that MTA stimulates the deposition of hard tissue, inducing apical formation, particularly in dental traumatology cases 8,13) . Due to its low toxicity and pH of 12.5, MTA has satisfactory biological properties and stimulates tissue repair 6,8,13) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MTA is a bioactive material that is mainly composed of tricalcium and silicate. Scientific investigations have shown that MTA can release various ions thatconduct and induct hard-tissue formation 4,17 .MTA presents some advantages,including its physical characteristics thatguarantee expansion during the attachment, which favors sealing, and the biological properties ofcalcium hydroxide 3,24 . MTA forms calcium oxide when in contact with water, which then, when in contact with tissue fluids, forms calcium hydroxide and triggers the same repair process in the tissue 11 .Some recentstudies have reported on the success of MTA as a root apical barrier, with rates ranging from 76.5% to 91% 10,20 .…”
Section: Discussionmentioning
confidence: 99%